2020
DOI: 10.1099/mic.0.000883
|View full text |Cite
|
Sign up to set email alerts
|

The signaling peptide PapR is required for the activity of the quorum-sensor PlcRa in Bacillus thuringiensis

Abstract: The transcriptional regulator PlcR, its cognate cell-cell signaling heptapeptide PapR7, and the oligopeptide permease OppABCDF, required for PapR7 import, form a quorum-sensing system that controls the expression of virulence factors in Bacillus cereus and Bacillus thuringiensis species. In … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 38 publications
0
6
0
Order By: Relevance
“…To confirm the epitope of the recognized HlyIIC-15, immunoblotting, wherein the interaction of antibodies along with HlyIICTD with recombinant proteins PlcR [9], HlyII, the deletion variant HlyIIΔC and HlyIIR (hemolysin II repressor) [10], as well as native hemolysin II B. cereus B771 cloned in Bacillus subtilis BD170 (Table 2), was used. In Fig.…”
Section: Resultsmentioning
confidence: 99%
“…To confirm the epitope of the recognized HlyIIC-15, immunoblotting, wherein the interaction of antibodies along with HlyIICTD with recombinant proteins PlcR [9], HlyII, the deletion variant HlyIIΔC and HlyIIR (hemolysin II repressor) [10], as well as native hemolysin II B. cereus B771 cloned in Bacillus subtilis BD170 (Table 2), was used. In Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Interestingly, newer studies have found a second quorum-sensing-system, consisting of PlcR-paralog PlcRa and the signaling peptide PapRa 7 , which is involved in oxidative stress response and cysteine metabolism. PapR variants were also able to activate PlcRa, which showed a connection between the PlcR and PlcRa regulons for the first time [250,251]. Recent studies focus on the inactivation of the PlcR-PapR quorum sensing system and, thus, the inhibition of virulence factor production due to synthetic PapR 7 derivatives.…”
Section: Enterotoxin Gene Expression and Toxin Secretionmentioning
confidence: 99%
“…However, a notable exception has been observed recently with the B. thuringiensis PlcRa regulator, a structural paralog displaying 29% sequence identity with PlcR (61). This RNPP regulator, involved in the oxidative stress response and cysteine metabolism, is activated during stationary phase by PapR, the cognate signaling peptide of PlcR, suggesting a high and unexpected versatility of PlcRa (62).…”
Section: Discussionmentioning
confidence: 99%